Methyl Jasmonate-Induced Changes of Flavor Profiles During the Processing of Green, Oolong, and Black Tea - Shi, Jiang; Xie, Dongchao; Qi, Dandan; Peng, Qunhua; Chen, Zongmao; Schreiner, Monika; Lin, Zhi; Baldermann, Susanne (Frontiers in Plant Science, 2019)
Tea aroma is one of the most important factors affecting the character and quality of tea. Here we describe the practical application of methyl jasmonate (MeJA) to improve the aroma quality of in teas. The changes of selected metabolites during crucial tea processing steps, namely withering, fixing and rolling, and fermentation, were analyzed. MeJA treatment of tea leaves (12h, 24h, 48h, and 168h) greatly promotes the aroma quality of green, oolong, and black tea products when comparing with untreated ones (0h) and as confirmed by sensory evaluation. MeJA modulates the aroma profiles before, during, and after processing. Benzyl alcohol, benzaldehyde, 2-phenylethyl alcohol , phenylacetaldehyde and trans-2-hexenal increased 1.07 to 3 -fold in MeJA-treated fresh leaves and the first two maintained at a higher level in black tea and the last two in made green tea. The This correlates with a decrease in aromatic amino acids by more than 2-fold indicating a direct relation to tryptophan- and phenylalanine-derived volatiles. MeJA-treated oolong tea was characterized by a more pleasant aroma. Eespecially the terpenoids (linalool and & oxides, geraniol, and carvenol increased) by more than 2-fold.